The possibility of applying Low Stress Stockhandling in reindeer - Simma, Ellen (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
The purpose of the study is to investigate the interest in Sami reindeer herders to use the Low Stress Stockhandling (LSS) method for handling reindeer. Also to find out which reindeer handling situations they think works the best and the worst, and which might need improvement. The purpose of LSS is to reduce the stress animals are subjected to during handling by creating consistent and calm responses from the animals. This is done by handling the animals through the animals’ point of view and using natural herd behavior to accomplish this. Data was collected through a ten question questionnaire distributed to reindeer herders. The questions intended to gain information on the background information about the participant, the aids used when managing reindeer, what handling situation the participants thought worked the best and worst the handling situation they believed is the most and least stressful for the reindeer, and if they thought that the stress reindeers are subjected to needs to be decreased. Other information collected included their thoughts about LSS and if they thought they would benefit from it during reindeer handling. Data received was complied together to get the total sum of all participants answers. 31 people answered the survey, 17 men and 14 women between the ages of 18and 52, with a mean age of 30. The aids used most were snowmobile and herding dog, and lasso was mostly used when capturing reindeer. When agreeing or disagreeing to the statement “There is a need to reduce the stress that reindeers are exposed to” on a seven point scale, where one was that they totally agreed and seven was that they totally disagreed; the mean value became 2,74. The handling situation that the participants thought worked the best was moving reindeer and the one that worked the worst was loading. The most stressful handling situation was also believed to be loading and the least stressful was gathering on bare ground. A majority of the participants (68%) thought that the LSS method could benefit them during reindeer handling. Loading and transportation was the handling situation participants found to be the most difficult, making loading a possible handling situation where LSS could be demonstrated and used by reindeer herders. Due to many managers involved in a reindeer herding district there can be difficulties in convincing everyone to participate in the new handling method. Reindeer are susceptible to handling stress. Therefore a reduction of the stress reindeers are exposed to during handling with LSS could benefit not only the reindeer, but also the reindeer herders and consumers of reindeer meat.